TECHNOLOGICAL FINANCE (FINTECH) AND ITS PERFORMANCE IN ALBANIA - Fabian Pjetri; Leonard Boduri; Rezart Dibra; Ilirjan Cukaj (Agora International Journal of Economical Sciences)
The main purpose of this paper presented by the authors has to do with the realization of an analysis on the progress and level of use of Financial Technology (FinTech) with a focus on the banking sector in the state of Albania. The notion of FinTech is a dedicated term for financial technology in the digital age. The diversity of this technological solution brings with it the promise of faster, cheaper, safer and more transparent financial transactions via the internet. In the paper carried out by the authors, primary data obtained from the completion of more than 500 questionnaires by individuals located in Tirana, Elbasan and Durres districts were used. Also, in this paper, other secondary data were used, which were provided by the base data of the Central Bank of the Albanian State, from the base data of the World Bank and the International Monetary Fund. This This paper describes the implications of policies regarding the promotion of relevant institutional policies regarding the increase in the level of use of Technological Finance in the state of Albania. The continued application of innovative technologies in finance and especially in the Fintech sector is very important, this will serve as a tool to increase the level of financial economic development in Albania (Toska, 2021). The findings underscore the potential for FinTech to foster financial inclusion and economic growth in Albania, provided that regulatory frameworks and digital infrastructures are strengthened. The paper presented by the authors also discusses financial policy implications and recommends some important measures that should be considered by the Albanian government and the Central Bank of Albania. By further stimulating the adoption and development of technological Finance in Albania, and by implementing international protocols regarding cyber security.